Ganglion cell distribution and retinal resolution in the Florida manatee, Trichechus manatus latirostris - Mass, A.; Ketten, Darlene; Odell, D.; Supin, A. (John Wiley & Sons, Inc., 2012)
The topographic organization of retinal ganglion cells was examined in the Florida manatee (Trichechus manatus latirostris) to assess ganglion cell size and distribution and to estimate retinal resolution. The ganglion cell layer of the manatee's retina was comprised primarily of large neurons with broad intercellular spaces. Cell sizes varied from 10 to 60 µm in diameter (mean 24.3 µm). The retinal wholemounts from adult animals measured 446-501 mm 2 in area with total ganglion cell counts of 62,000-81,800 (mean 70,200). The cell density changed across the retina, with the maximum in the area below the optic disc and decreasing toward the retinal edges and in the immediate vicinity of the optic disc. The maximum cell density ranged from 235 to 337 cells per millimeter square in the adult retinae. Two wholemounts obtained from juvenile animals were 271 and 282 mm 2 in area with total cell numbers of 70,900 and 68,700, respectively (mean 69,800), that is, nearly equivalent to those of adults, but juvenile retinae consequently had maximum cell densities that were higher than those of adults: 478 and 491 cells per millimeter square. Calculations indicate a retinal resolution of ~19' (1.6 cycles per degree) in both adult and juvenile retinae.